UNJUK KERJA MEKANISME FAIRNESS MENGGUNAKAN METODE SCHEDULING PADA KANAL UPSTREAM SISTEM CATV - Sueb
Abstrak: To provide an added value for CATV customer with internet access, CATV operator should optimize the existing infrastructure due to its minimum cost. The CATV infrastructure usually has tree and branch topology in which if it is used for internet access in residential area will create an unfair condition to CATV services customer. It is necessary to control the packet flow which will be processed in server using scheduling method so that the packet sending from all customer segmentation have the same probability to achieve headend. In this thesis, it is used the flow control mechanism using Scheduling method as a solution to create a fairness in all customer segmentation based on geographical area, then it is compared with a method using FIFO (First In First Out) discipline. Both methods will be simulated to get the performance of 10 Mbps access of upstream channel CATV system. The performance parameters that observed are the packet loss probability and average delay from each customer segmentation. By using Scheduling method, it is expected to provide a result which shows that the packet loss probability in each customer segmentation is almost the same. It also means that every cable segment has the same probability to achieve headend. The experiment of each method is done by simulation using various of traffic load i.e. 0.025 Erlang, 0.075 Erlang, 0.125 Erlang, 0.175 Erlang, 0.225 Erlang, 0.275 Erlang, 0.325 Erlang, 0.375 Erlang, and 0.425 Erlang and various of buffer capacity (4, 8, 12, 16, and 20). The simulation result of Scheduling method show that the higher the traffic load the higher the packet loss probability and delay. Cable segment position doesn\'t almost influence on packet loss probability but influence little bit on average delay which trends little bit decreasing if cable segment position increase. The highlower.